Gravidez na adolescência e aborto: Implicações da ausência de apoio familiar - De Moraes, Eleomar Vilela; De Toledo, Olegário Rosa [UNESP]; David, Flávia Lúcia; Avelino, Mariza Martins; Campos, Rodolfo Nunes (My University, 2017)
Objective: Investigate the socio-cultural characteristics and risk factors related to abortion among pregnant adolescents with 10-19 years-old, assisted by the Unique Health System from Medium Araguaia. Methods: This is a cross seccional, descriptive and non probabilistic epidemiological study. We investigated 101 pregnant adolescents assisted by the Medium Araguaia Unified Health System. The data were analyzed using the chi-square test and the occurrence of the events calculated by odds ratio. Results: The median age was 17 years and 11% from the interviewees had up to 14 years and approximately half of them studied until the eighth grade. Abortion incidence increased significantly according to the rejection of pregnancy by the family (OR = 23.33), having more than two partners (OR = 10.22), illicit drug use (OR = 9.77) and smoking during pregnancy (OR = 6.69). Conclusions: The lack of support, the absence of bonding with the partner, the low self-esteem and detachment to the child in formation, seem destabilize deeply the adolescent, who now consider abortion as a viable alternative.
Adolescent pregnancy and abortion: Implications of absence of family support
Keywords: Alcohol drinking; Maternal-fetal relations; Street drugs